Bats from the classical site of Venta del Moro (Late Miocene, Eastern Spain). (3rd April 2018) - Crespo, Vicente D.; Sevilla, Paloma; Mansino, Samuel; Montoya, Plinio; Ruiz-Sánchez, Francisco Javier
Abstract: The presence of bat fossils in localities of fluvio-lacustrine origin is quite uncommon, and usually these remains are poorly preserved or not studied in detail. In the present work we study the bat association of the classical Late Miocene locality of Venta del Moro, which have yielded remains of five taxa of chiropterans. Two new bat species are described in this work: Pipistrellus rouresi sp. nov., a new form to the extremely scarce Neogene register of pipistrelle bats, and the horseshoe bat Rhinolophus antonioi sp. nov. Additionally, we describe the oldest and southernmost record of Myotis podlesicensis, a mouse-eared bat of African origin, as well as an undetermined taxon belonging to the noctule bats, Nyctalus sp., and a further taxon of Vespertilionidae indet. With the description of this new material, the record of Late Miocene bats from Europe is increased. http://www.zoobank.org/urn:lsid:zoobank.org:act:3B41C73D-9C09-46DA-A77C-1C6F1FB0F014 http://www.zoobank.org/urn:lsid:zoobank.org:act:82B8A593-6DF5-4CD4-820D-7279E3C6C9D1